Knowledge Co-construction by Citizens and Researchers to Create a SNAPSHOT of the Marine Environment During and After the Covid-19 Lockdown - Giuffredi, Rita; Criscuolo, Laura; De Lazzari, Amelia; Fanelli, Giovanni; Giordano, Raffaele; Petrocelli, Antonella; Portacci, Giuseppe; Pugnetti, Alessandra; L’Astorina, Alba (Frontiers in Marine Science, 2021)
Lockdown measures adopted in Italy to contain the diffusion of Covid-19 altered many variables influencing the anthropogenic pressure on marine ecosystems. Public reactions included surprise at how quickly changes in human activity seemingly improved natural recovery and, at the same time, a generalised anxiety to restart economic activities. In this situation several Institutions from the Italian National Research Council (CNR) made a joint effort to quantify the effects of the unprecedented experimental conditions induced by the reduction of many anthropogenic pressures. The resulting project was conceived with a holistic, interdisciplinary approach, geared to combine scientific, economic and cultural observations to promote collective actions suitable to the governance of socio-ecological systems, reconciling respect for the environment with human activities and wellbeing, and thus grounding an ethical approach to marine resources. Alongside collecting considerable amount of scientific observations, the project is working to complement samplings and analyses with the non-formal knowledge carried by the inhabitants of a set of coastal zones, thus enriching the generated knowledge and widening inclusion and pluralism in defining the challenges at stake; simultaneously it focuses on stimulating a reflection in the research community over the process of knowledge co-construction, its meaning, role and responsibility in the societal context. After a brief contextualization of this activity, we present here the perspective adopted by researchers to build a responsible marine research plan. We comment the community-related features, explore limits and opportunities, and propose a set of recommendations, based on a preliminary review of our experiences.